2002
DOI: 10.1258/0022215021910195
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic orbital decompression for Graves’ ophthalmopathy

Abstract: Graves' disease may occasionally result in signi cant proptosis that is either cosmetically unacceptable or causes visual loss. This has traditionally been managed surgically by external decompression of the orbital bony skeleton. Trans-nasal endoscopic orbital decompression is emerging as a new minimally-invasive technique, that avoids the need for cutaneous or gingival incisions. Decompression of the medial orbital wall can be performed up to the anterior wall of the sphenoid sinus. This can be combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
4
18
0
1
Order By: Relevance
“…Our experience of a mean regression of proptosis of about 3.70 mm is similar to what has been reported in previous studies adopting a similar approach[89101112131415] [Table 4] and comparable to the reduction of 3 to 5.5 mm reported from the non-endoscopic Walsh Ogura technique. [1617]…”
Section: Discussionsupporting
confidence: 89%
“…Our experience of a mean regression of proptosis of about 3.70 mm is similar to what has been reported in previous studies adopting a similar approach[89101112131415] [Table 4] and comparable to the reduction of 3 to 5.5 mm reported from the non-endoscopic Walsh Ogura technique. [1617]…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the horizontal distances from the MOF to the ION at the depth of the AE and BL were approximately more than 10 mm. Those results could support the concept that it would be difficult to injure the ION by orbital floor removal in endoscopic orbital decompression [15]. …”
Section: Discussionsupporting
confidence: 54%
“…The ION is used as the landmark for endoscopic orbital decompression and endoscopic approach of the pterygopalatine fossa [15,16]. In our study, the horizontal distances from the MOF to the ION at the depth of the AE and BL were approximately more than 10 mm.…”
Section: Discussionmentioning
confidence: 59%
“…The Caldwell-Luc procedure combined with endoscopy is described by Rizk et al [27], who identified the infraorbital nerve before removing the median portion of the orbital floor of the orbit. The pathway of the infraorbital triad is used as an important landmark during endoscopic orbital decompression for thyroid ophthalmopathy such as the Walsh-Ogura procedure [2,17,31]. It is emphasised that the region of the infraorbital canal and groove is crucial in surgical reconstructions [1].…”
Section: Discussionmentioning
confidence: 99%